2002
DOI: 10.1124/dmd.30.6.658
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioavailability and Metabolism with Two Commercial Formulations of Cyclosporine A in Rats

Abstract: ABSTRACT:The bioavailability and metabolism of cyclosporine A (CsA) capsules were compared with two bioequivalent (Food and Drug Administration approved) preparations in rats. Two groups of WistarKyoto rats were given 10 mg/kg q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The use of healthy volunteers, rather than patients, to determine the bioequivalence of immunosuppressants has recently been criticized (36) and evidence is now becoming available to show that there are differences in metabolism between formulations (37), that independent researchers are unable to confirm bioequivalence of formulations in repeated studies Data set 2302a had the data from one subject and 2302b data from two subjects omitted from the data, in line with FDA guidance, due to high predose MPA concentrations. (38), and that therapeutic equivalence has not been shown for some formulations (39).…”
Section: Discussionmentioning
confidence: 93%
“…The use of healthy volunteers, rather than patients, to determine the bioequivalence of immunosuppressants has recently been criticized (36) and evidence is now becoming available to show that there are differences in metabolism between formulations (37), that independent researchers are unable to confirm bioequivalence of formulations in repeated studies Data set 2302a had the data from one subject and 2302b data from two subjects omitted from the data, in line with FDA guidance, due to high predose MPA concentrations. (38), and that therapeutic equivalence has not been shown for some formulations (39).…”
Section: Discussionmentioning
confidence: 93%
“…Koehler et al reported that the bioavailability of a CsA generic product (Eon Labs) in rats was lower than that of Neoral, whereas the plasma AM4N level was significantly elevated in groups receiving Eon compared to that in another group receiving Neoral. 17) In our data, a significantly elevated AM4N blood level was not observed in groups treated with generic products compared with that of the group treated with Neoral, Product B. In rats, CsA undergoes first-pass metabolism by CYP3A, which is located in the gastrointestinal mucosa and in the liver.…”
Section: Pharmacokinetics Of Csa and Its Metabolites In Ratsmentioning
confidence: 65%
“…16) In addition, another group reported that after oral administration in rats, the pharmacokinetics of CsA metabolites differed between the innovator and generics. 17) Thus, as we describe above, there are concerns about the quality and efficacy of generics due to the formulation specificity of the innovator and the narrow therapeutic window of CsA. To our knowledge, there have been no direct comparisons of innovator and generics using both in vitro and in vivo assessment.…”
mentioning
confidence: 99%
“…Although a number of bioequivalent assessments for various drugs were conducted in the rat model [27-29], considerable variability of drug level in population or series time points sampling have been observed in early studies, which has hampered the precision of bioequivalence studies [30-32]. Recently, in spite of the many successful reports of bioequivalence/bioavailability studies in rats by using microdialysis, there are a few challenges that need to be addressed before microdialysis can be regarded as a generally applicable routine technique for assaying drug delivery [33].…”
Section: Resultsmentioning
confidence: 99%